La moneda navarra en la Edad Moderna, problemas documentales. Tipos y leyendas. - Francisco Olmos, José María de (Revista General de Información y Documentación, 2000)
Study of the Documental importance of of Navarrese coin in the Modern Age. Its importance as a political propaganda for both parts: the French and the Spanish; its modifications along the time, specially in the time of Felipe V aud its desappearance in te time of Isabel II.
Keywords: Numismatics Money Navarre; XV-XIX centuries; political propagan da